Association of glycated haemoglobin (HbA1C) level with working memory on type-2 diabetes mellitus and prediabetic patients - Sastrawan, Muhammad Gandhi; Sjahrir, Hasan; Iqbal, Kiki Mohammad (International Journal of Research in Medical Sciences, 2019)
Background: Deleterious effects of diabetic glucose levels on brain structure, have been reported in many studies. Moreover, prediabetic and type-2 diabetes mellitus are associated with lower cognitive function. Author aimed to discover the association of blood glucose and working memory on type 2 diabetic and prediabetic patients. Methods: In this cross-sectional study there are two groups (diabetic and prediabetic) consist of 30 patients each (men 31, women 29). Mean age 40.233±7.862. Blood glucose was measured with HbA1c. All patients were tested with MMSE (Mini Mental State Examination), forward digit span, and backward digit span. Results: There was no difference between diabetic and prediabetic group in MMSE (p 1.000). In diabetic group, mean LDSF (Longest Digit Span Forward) was 5.700±0.877 and there was relation between HbA1c and LDSF (r -0.604). In prediabetic group, mean LDSF was 6.233±0.858 and there was relation between HbA1c and LDSF (r -0.565). There was significant difference between those groups in LDSF (p 0.041). In diabetic group mean LDSB (Longest Digit Span Backward) was 3.767±0.817 and there was relation between HbA1c and LDSB (r -0.545). In prediabetic group, mean LDSB was 4.300±0.750 and there was relation between HbA1c and LDSB (r -0.575). There was significant difference between those groups in LDSB (p 0.024). Conclusions: Results indicated that there was significant difference between diabetic and prediabetic patient in working memory test although there was no difference in general cognitive function.